ENERGY DIPLOMACY AND GLOBAL COLLABORATION: INDODEPP'S ROLE IN FACILITATING INDONESIA'S ENERGY TRANSITION - Hastuti, Ika Sri; Windary, Shylvia; Mukti , Muhammad Fahmi (Universitas Budi Luhur, 2025)
Abstract: In Indonesia's energy diplomacy and sustainable development policy, energy transition is a strategic issue. The goal of the Indonesia-Denmark Energy Cooperation Program (INDODEPP) is to promote clean energy transition in Indonesia. In the context of bilateral cooperation in the field of renewable energy, this study will explain the implementation and barriers to implementation. The research method used is descriptive analysis using secondary data from official government documents, cooperation reports, news, and scientific literature related to INDODEPP. Data analysis techniques used include data reduction, data presentation, and conclusion drawing. The results show that the program has achieved many good things, such as the creation of the Energy Transition Roadmap and technical assistance in the renewable energy sector. However, there are several things that hinder the implementation of INDODEPP, such as the incompatibility of national and local policies, limited institutional and technical capacity at the local level, and problems in coordination between stakeholders. As a result, the Indonesia-Denmark Energy Cooperation Program (INDODEPP) is a strategic effort to support the transformation of the national energy sector towards a cleaner, more sustainable and efficient energy system. The ability of the parties to overcome structural and institutional barriers is an important factor in this program. Therefore, in order for this cooperation to make a real contribution to realizing the energy transition in Indonesia, cross-sector policy harmonization and technical capacity building at the regional level are needed. Abstrak: Dalam diplomasi energi dan kebijakan pembangunan berkelanjutan Indonesia, transisi energi adalah isu strategis. Tujuan dari Indonesia – Denmark Energy Cooperation Program (INDODEPP) adalah untuk mempromosikan transisi energi bersih di Indonesia. Dalam konteks kerja sama bilateral di bidang energi terbarukan, studi ini akan menjelaskan pelaksanaan dan hambatan dalam pelaksanaannya. Metode penelitian yang digunakan adalah analisis deskriptif menggunakan data sekunder dari dokumen resmi pemerintah, laporan kerjasama, berita, dan literatur ilmiah terkait INDODEPP. Teknik analisis data yang digunakan meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasilnya menunjukkan bahwa program ini telah mencapai banyak hal baik, seperti pembuatan Energy Transition Roadmap dan bantuan teknis di sektor energi terbarukan. Namun, ada beberapa hal yang menghambat pelaksanaan INDODEPP, seperti ketidakcocokan antara kebijakan nasional dan lokal, kapasitas kelembagaan dan teknis yang terbatas di tingkat lokal, serta masalah dalam koordinasi antara pemangku kepentingan. Oleh sebab itu, Indonesia-Denmark Energy Cooperation (INDODEPP) adalah upaya strategis untuk mendukung transformasi sektor energi nasional menuju sistem energi yang lebih bersih, berkelanjutan, dan efisien. Kemampuan para pihak untuk mengatasi hambatan struktural dan kelembagaan adalah faktor penting dalam program ini. Oleh karena itu, agar kerja sama ini dapat memberikan kontribusi nyata dalam mewujudkan transisi energi di Indonesia, diperlukan harmonisasi kebijakan lintas sektor dan pembangunan kapasitas teknis di tingkat regional.